Escrita (auto)biográfica e círculo de leitura literária no desenvolvimento do letramento racial crítico com jovens do ensino médio - Figueiredo, Victor Matheus Gonçalves de (2022)
The practice of critical race literacy for the understanding of the formation of ethnoracial identities is the object of study of this dissertation. The objective is to understand the contributions of critical race literacy and (auto)biographical narratives to the affirmation of the identities of young participants of the group Ethno-Literatures. The school as a formal educational institution, regulated by the State, is a place of reproduction of a prevailing order that represents the black in a certain way, raising the question about the role of school in the teaching of Afro-Brazilian culture and the impacts for the affirmation of the identities of students. Besides understanding that the school reinforces and reproduces the racist structures present in Brazilian society. From the conception of critical race theory, the practices of racial literacy make it possible to question the performance of the school for ethnoracial relations. The methodology used in this research will be the (auto)biographical narratives, where the speeches and life trajectories of the reading group participants will be analyzed. Through this method it will be possible to reflect through the writings and speeches of the students the training for ethnoracial relations.